Dynamics in car ownership: the role of entry into parenthood - Abu Toasin Md Oakil; Dorien Manting; Hans Nijland (European Journal of Transport and Infrastructure Research, 2016)
This study investigates the impact of entry into parenthood on changes in car ownership. If entry into parenthood affects changes in car ownership, then delay or offset of entry into parenthood might also be an important explanation of recent car travel trends of young adults. This study analysed the impact of entry into parenthood on changes in the number of cars per household. Also, attention is given to the role of other related life course changes such as a change in urbanisation level, employment or household income. Using a unique data set, in which register data from 2011 and 2013 on the Dutch population, income and vehicle registration were combined, the study revealed that couples are more likely to enter car ownership and less likely to exit car ownership when they enter into parenthood. This implies that the delay of entry into parenthood might lead to later entry into car ownership and an increase in life time childlessness might lead to an overall decline in car ownership.